DNA repair foci and late apoptosis/necrosis in peripheral blood lymphocytes of breast cancer patients undergoing radiotherapy. (2nd December 2015) - Marková, Eva; Somsedíková, Alexandra; Vasilyev, Stanislav; Pobijaková, Margita; Lacková, Alica; Lukačko, Pavol; Belyaev, Igor
Abstract: Purpose : Double-strand breaks (DSB) repair and apoptosis are assumed to be key factors in the determination of individual variability in response to radiation treatment. In this study we investigated tumor protein p53 (TP53) binding protein 1 (53BP1) and phosphorylated histone 2A family member X (γH2AX) foci, γH2AX pan-staining and late apoptosis/necrosis (LAN) in lymphocytes from breast cancer (BC) patients undergoing radiotherapy. Materials and methods : BC patients were subjected to local radiotherapy with fractionated doses using linear accelerator. Adverse reactions of patients were classified according to the Radiation Therapy Oncology Group (RTOG)/European Organization for Research and Treatment of Cancer (EORTC) criteria. Blood samples were collected before treatment, at various time-points during and after radiotherapy. Residual 53BP1 and γH2AX foci, γH2AX pan-staining were analyzed in peripheral blood lymphocytes (PBL) using the Metafer system and confocal laser scanning microscopy. LAN cells were counted by the trypan blue (TB) exclusion assay. Statistical analysis was performed using Mann–Whitney test, Spearman rank correlation test and analysis of covariance (ANCOVA). Results : No statistically significant changes were observed in the levels of γH2AX foci during radiotherapy. In contrast, radiation-induced residual 53BP1 were detected already after the first fraction. Increased individual variability in the 53BP1 focus formation was observed during treatment. The background level of DNA repair foci and its individual variability in response to radiotherapy decreased after the end of radiotherapy indicating successful removal of DNA-damaging effects. A correlation between stage of cancer and 53BP1 focus formation was established which suggests the prognostic value of this test. We show that the fraction of LAN cells negatively correlates with the level of 53BP1 and positively correlates with individual radiosensitivity. Only weak correlation was observed between γH2AX pan-staining and LAN cells. Due to large interindividual variability, both in vivo assays, LAN and focus formation, have shown relatively low predictive power at the individual level. Conclusions : It is likely that radiosensitive patients have less efficient mechanisms of elimination of apoptotic cells with DNA damage resulting in accumulation of LAN cells and facilitating adverse reactions. Our data suggested that the grade of adverse reaction may positively correlate with LAN cells in PBL before and during radiotherapy.